Distance Learning for Higher Education Applicants in War: Information Competence - Truba, H.; Radziievska, I.; Sherman, M.; Morska, N.; Kulichenko, A. K.; Havryliuk, N.; Куліченко, Алла Костянтинівна (My University, 2022)
Modern challenges in the educational environment force scientists and practitioners to search for an adequate answer. In particular, the war in Ukraine demonstrated the importance of developing information competence as one of the main means of distinguishing true information from a whole stream of fake news. This is especially relevant in connection with the introduction of distance learning when students must find and process a large amount of information on their own. Therefore, the purpose of the article is to analyze the training of higher education students through the prism of acquiring the necessary level of informational competence in war conditions. For this, general scientific and special research methods, as well as the experimental method, were used. In the results, the peculiarities of the interpretation of information competence in the distance form of education among modern researchers are determined, the psychological components of resistance to fakes are analyzed. Based on the conducted empirical measurements, it was established that thorough work on student education gives positive skills when working independently with Internet materials, strengthens the ability to distinguish false information and propaganda from the real state of affairs. The conclusions summarize the results of the empirical research and suggest ways to improve the situation with the formation of information competence.
Kulichenko A. K. - ОRCID ID: 0000-0003-1469- 3816
Keywords: high education; competencies; war; Internet; psychology